Peningkatkan Minat Siswa dalam Menulis Cerita Fiksi melalui Media Gambar pada Siswa Kelas V SDS Al Washliyah 31 Medan Labuhan - Nurwahyuni Nurwahyuni; Belia Tama Heppi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Writing fiction stories is one of the important language skills in learning Indonesian. However, students' interest in writing fiction stories is still low, especially in Class V of SD S Alwashliyah 31 Medan Labuhan. One of the main causes is the lack of learning methods that attract and motivate students. Therefore, this research aims to increase interest and skills in writing fiction stories using image media. The research method used is descriptive analytical, namely a study that aims to collect data, describe, process, analyze, conclude and interpret data in order to obtain a systematic picture. The subjects of this research were 30 class V-A students in semester 1 of the 2024-2025 academic year. The data collection instruments used include competency tests and observation sheets. Competency tests are used to measure student learning outcomes after learning takes place using image media, while observation sheets are used to assess the implementation of class actions, class conditions, and student activity in the learning process. The research results show that image media can increase creativity, motivation, and help students compose more structured stories. This research is expected to provide insight for teachers in implementing more effective learning methods to improve students' writing skills.